Exploration of the Characteristics of Intestinal Microbiota and Metabolomics in Different Rat Models of Mongolian Medicine. (3rd August 2021) - Dao, Riao; Wu, Dongxing; Wang, Huan; Jin, Habur; Li, Li; Fu, Xiquan; Sa, Chula; Eerdunchaolu,
Abstract : Background . Mongolian medicine is a systematic theoretical system, which is based on the balance among Heyi, Xila, and Badagan. However, the underlying mechanisms remain unclear. This study aimed to explore the characteristics of intestinal microbiota and metabolites in different rat models of Mongolian medicine. Methods . After establishing rat models of Heyi, Xila, and Badagan, we integrated 16S rRNA gene sequencing and metabolomics. Results . Heyi, Xila, and Badagan rats had significantly altered intestinal microbial composition compared with rats in the MCK group. They showed 11, 18, and 8 significantly differential bacterial biomarkers and 22, 11, and 15 differential metabolites, respectively. The glucosinolate biosynthesis pathway was enriched only in Heyi rats; the biosynthesis of phenylpropanoids pathway and phenylpropanoid biosynthesis pathway were enriched only in Xila rats; the isoflavonoid biosynthesis pathway, the glycine, serine, and threonine metabolism pathway, and the arginine and proline metabolism pathway were enriched only in Badagan rats. Conclusions . The intestinal microbiota, metabolites, and metabolic pathways significantly differed among Heyi, Xila, and Badagan rats compared with control group rats.